Protecting groundwater in intensive agricultural areas through irrigation with treated wastewater: focus on nitrate, salt, and Escherichia coli - Barbara Casale; Angela Libutti; Carlo Salerno; Giovanni Berardi; Pompilio Vergine (Cleaner Water)
A set of 4 soil column duplicates was irrigated with treated wastewater to study the possible leaching of nitrate, salt, and Escherichia coli to groundwater. The reclaimed water was a municipal secondary effluent, stored for 5 days to attenuate microbial contamination. It had nitrate concentration of 36.1±4.9 mgN/L, electrical conductivity of 1.6±0.1 mS/cm, and E. coli content between 36 and 918 MPN/100 mL (median value of 194 MPN/100 mL). Soil column tests were carried out over a period of 80 days, considering both the cultivation of a typical Mediterranean crop (pepper) and the edge case of non-cultivated soil. Nitrate and salt were up-taken by crops for around 90% and 50%, respectively, while they leached through non-cultivated soil according to linear relationships, with nitrate moving faster than salts. Due to its natural decay, E. coli never reached 66 cm depth. Crop irrigation with reclaimed water can be managed so as not to cause significant leaching of E. coli and nitrate, even though it may result in a small leaching of salt. Replacing groundwater with reclaimed water as an irrigation source should be considered as a possible action to protect aquifers, and especially those suffering from saline contamination, from the effects of overexploitation and overfertilization practices.